Home again [compact disc] - Kiwanuka, Michael, 1988- (Interscope Records : Universal Music Distribution, 2012)
Home Again was produced by Paul Butler in his vintage equipment-stuffed basement studio at his house in Ventnor on the Isle of Wight. Together, Butler and Kiwanuka played almost every instrument to be heard on the album, with Butler's intimate, detailed productions, adorned with everything from flute to brass to sitar to aching strings, perfectly matching Kiwanuka's visions for his songs.